2000
DOI: 10.1063/1.480513
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally resolved photoelectron spectroscopy of the first row transition metal and C3 clusters: MC3− (M=Sc, V, Cr, Mn, Fe, Co, and Ni)

Abstract: We report photoelectron spectra of the MC 3 Ϫ clusters for MϭSc, V, Cr, Mn, Fe, Co, and Ni at two photon energies, 355 and 266 nm. Vibrational structure is resolved for the ground and excited state detachment transitions for all the clusters except for CoC 3 Ϫ and NiC 3 Ϫ. Electron affinity ͑EA͒ and vibrational frequencies for the MC 3 clusters are obtained. Complicated low-lying excited state features are observed for all the species. We find that the trend of the EA across the 3d series for the MC 3 clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The theoretical characterization of the interaction among a few carbon and iron atoms has been approached in several manners. One of them deals with a single iron atom interacting with a small amount of carbon atoms. Reports on the dimer FeC and FeC n ( n = 2–10) clusters are a few examples of this category. Another point of view treats with interactions among a few iron and carbon atoms that are structurally mixed.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical characterization of the interaction among a few carbon and iron atoms has been approached in several manners. One of them deals with a single iron atom interacting with a small amount of carbon atoms. Reports on the dimer FeC and FeC n ( n = 2–10) clusters are a few examples of this category. Another point of view treats with interactions among a few iron and carbon atoms that are structurally mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on transition metal carbide clusters have been performed by using both experimental and theoretical methods. Photoelectron spectroscopy has been known as a popular experimental technique which can be employed to probe the relative energetic positions of low-lying electronic states. In the literature, a large number of photoelectron spectra of transition metal carbide clusters have been reported. Also, quantum chemical calculations have been proven to be vital for acquiring the geometric and electronic structures of these kind of clusters. , It is well-known that they show strong electron correlation and multireference wave effects, which implies the need for highly accurate computational methods such as coupled-cluster theory (CCSD­(T)), complete active space second-order perturbation theory (CASPT2), and multireference configuration interaction (MRCI). ,,, In many cases, the computational results turned out to be essential for assigning the anion photoelectron spectra. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al . 31 reported photoelectron spectra of FeC 3 − cluster, and found that the ground states of FeC 3 and FeC 3 − clusters have C 2v ring structures. Using gas phase ion chromatography, Helden et al .…”
Section: Introductionmentioning
confidence: 99%